2005
DOI: 10.1002/eji.200526059
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and phenotype of murine rotavirus-specific B cells induced by intranasal immunization with 2/6 virus-like particles

Abstract: Virus-like particles containing the rotavirus (RV) internal proteins VP2 and VP6 (2/6-VLP) have been shown to induce serum and fecal antibodies as well as protection in mice after intranasal administration with a mutant of E. coli toxin, LT-R192G. To better understand the origin of fecal IgA induced by this protocol, we studied the RV-specific B cell response in systemic and mucosal lymphoid tissues using a flow cytometry assay that allows quantification and phenotypic characterization of RV-specific B lymphoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 31 publications
2
19
1
Order By: Relevance
“…A similar profile has been reported for RV-specific B cells during natural RV infection in children (23). By contrast, it was recently shown that intranasal immunization with 2/6-VLP did not induce a significant number of RV-specific B cells with an intestinal homing profile (38). In our model, most of our vaccine regimens induced coproantibodies to RV.…”
Section: Vol 80 2006 Rectal Immunization With Rv Vlp In Mice 1757mentioning
confidence: 58%
“…A similar profile has been reported for RV-specific B cells during natural RV infection in children (23). By contrast, it was recently shown that intranasal immunization with 2/6-VLP did not induce a significant number of RV-specific B cells with an intestinal homing profile (38). In our model, most of our vaccine regimens induced coproantibodies to RV.…”
Section: Vol 80 2006 Rectal Immunization With Rv Vlp In Mice 1757mentioning
confidence: 58%
“…More recently, a study with mice showed that i.n. immunization with 2/6-VLPs induced a high frequency of RV-specific B cells in the respiratory lymphoid tissue and spleen, but only a minor fraction of them expressed the ␣ 4 ␤ 7 integrin (40). Taken together, these results may explain why the administration of antigens by the i.n.…”
Section: Discussionmentioning
confidence: 81%
“…RV infects mature enterocytes of the small intestine causing gastroenteritis and represents a good viral model of mucosal infection and thus of mucosal immunization. In a previous work [4], we used the same method as Youngman et al [3], based on RV GFP-virus-like particle (VLP) binding, to trace RV-specific B cell responses in respiratory and intestinal lymphoid tissues after intranasal (IN) immunization of mice with VLP in the presence of mucosal adjuvant. This strategy has been shown to confer protection against RV infection [5].…”
Section: Introductionmentioning
confidence: 99%